Can legumes improve the productivity and resilience of semi-arid Kenyan grasslands via influence on soil processes? - Pearce, F.; Leitner, Sonja (International Livestock Research Institute, 2025)
Semi-arid savanna grasslands in Kenya are vital for food production and rural livelihoods, with livestock grazing accounting for more than 90% of household incomes in arid and semi-arid areas. However grassland soils have become degraded in many areas due to vegetation loss and soil erosion, often caused by overgrazing. Soil degradation (depletion of organic matter and nutrient levels, disrupted soil biological process, and poor structure) reduces plant productivity and resilience to extreme weather conditions such as drought. Given that drought has been increasing in severity, duration and frequency over recent decades, this has severe implications for food security across sub Saharan Africa.